Effect of dipyridamole and adenosine monophosphate on cell proliferation in the hemopoietic tissue of normal and gamma-irradiated mice - Pospísil, M; Hofer, M; Netíková, J; Viklická, S; Pipalová, I; Bartonícková, A (Experientia, 1992)
Combined treatment with dipyridamole and adenosine monophosphate enhances cell proliferation in the hemopoietic tissue of normal and gamma-irradiated mice. This effect can be explained by the elevation of extracellular adenosine, and the receptor-mediated activation of the cell adenylate cyclase system.
Keywords: adenosin; dipyridamol; Mice, Inbred CBA; Male; slezina; buňky kostní dřeně; Adenosine Monophosphate; mužské pohlaví; buněčné dělení; krevní buňky; Gamma Rays; Spleen; Blood Cells; Dipyridamole; Animals; Cell Division; adenosinmonofosfát; zvířata; myši inbrední C57BL; myši; Mice, Inbred C57BL; Adenosine; Mice; záření gama; Bone Marrow Cells; myši inbrední CBA